Kolaborasi Stakeholder dalam Perencanaan Program Kota Tanpa Kumuh (KOTAKU) di Kecamatan Jaten Kabupaten Karanganyar - Rifki Rositasari; Asal Wahyuni Erlin Mulyadi (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
One of the slum alleviation programs is the KOTAKU (City Without Slums) program. The KOTAKU program was initiated in Indonesia since 2015, this program was organized to deal with issues of the year through a collaborative platform. The purpose of this study was to determine the process of stakeholder collaboration in the Kotaku planning program in Jaten District, Karanganyar Regency. In addition, it also analyzes what factors affect the achievement of results in the planning of the KOTAKU program. This study analyzes using the collaboration process theory from Ansell and Gash. The approach used is descriptive qualitative. Data collection techniques through interviews and documentation. The results of the study indicate that at the planning stage of KOTAKU in the District of Jaten, collaborations have been carried out by various stakeholders which have been going well. However, along the way, a number of obstacles were encountered. The collaboration process is carried out starting from face-to-face dialogue, trust building, commitment to the process, Share understanding and Intermediate outcomes. There are factors that influence collaboration, namely the driving and inhibiting factors. The driving factor for collaboration is socialization and stakeholders are joint factors in identifying problems. Meanwhile, the inhibiting factors are differences of opinion and time constraints.